(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to study the role of applying function-based cost analysis in competitive pricing decisions, by applying it in the General Company for Leather and Textile Industries, specifically the leather factory in Baghdad (leather shoe factory). To achieve this goal, the researchers relied on the deductive approach through the use of sources, periodicals, and references. Arabic and foreign, and the inductive approach through multiple means, including accounting records, cost reports, questionnaires, field experience, and interviews. The researchers reached conclusions, the most important of which is that applying cost analysis based on function in the unit (research sample) has a positive and effective role in improving and reducing the cost of production without affecting quality. This, in turn, led to reducing the selling price and improving the competitive pricing decision. The most important recommendation is urging the economic unit (the General Company for Leather and Textile Industries) to apply cost analysis based on function because of its effective role in improving and making appropriate competitive pricing decisions in light of the intense competition in the local markets. Which improves the unit’s economic position and increases market share.